Pengaruh PDRB, Pendidikan Dan Struktur Tenaga Kerja Terhadap Kemiskinan Di Kota Bukittinggi - Saputra, Hendri Andika; Ginting, Dastanta Irvan (ITB AAS INDONESIA Surakarta, 2024)
This research aims to analyze the influence of Gross Regional Domestic Product (GRDP), education level, and workforce structure on poverty levels in Bukittinggi City. The data used in this research is secondary data obtained from the Bukittinggi City Central Statistics Agency and other related agencies. The analytical method used is multiple regression with the Ordinary Least Square (OLS) model. The research results show that GRDP per capita, education level, and workforce structure together have a significant effect on the poverty level in Bukittinggi City. Individually, GRDP per capita and labor structure have a negative effect on poverty, while education level has a positive effect on poverty. This shows that increasing GRDP per capita and the labor structure of the agricultural sector can reduce poverty levels, while the level of education has not been able to reduce poverty